PENGARUH MOTIVASI TERHADAP KINERJA TIM TINDAK LANJUT PADA INSPEKTORAT KABUPATEN MAMUJU UTARA - Iskandar, Ishar (Katalogis, 2016)
The aim of this study; (1) to determine the effect of physiological needs, safety needs, social needs, esteem needs and self-actualization needs simultaneously (synchronously) on the performance of the follow-up team in North Mamuju District Inspectorate; (2) to determine the effect a partial physiological needs (people) on team performance follow-up; (3) the effect of the partial safety needs (people) on team performance follow-up; (4) the effect of the partial social needs (people) on team performance follow-up; (5) the effect of the partial award needs (people) on team performance follow-up; (6) the effect of partially self-actualization needs (people) to follow up the performance of the team. This type of research is quantitative descriptive and verification approach. This study population Inspectorate Team Follow-up on the North Mamuju regency with the number 40 with census sampling techniques so that the entire population sampled. Data collection techniques including observation, questionnaires, and documentation, while the technique of data analysis using multiple linear regression. The results showed; (1) physiological needs, safety needs, social needs, esteem needs and self-actualization needs simultaneously (in unison) affect the team's performance follow-up to the Inspectorate of North Mamuju regency, with the effect of 80.2% and the degree of relationship very strong; (2) the physiological needs partial (individual) effect on the performance of the team follow-up; (3) safety needs partial (individual) effect on the performance of the team follow-up; (4) social needs partial (individual) effect on the performance of the team follow Further; (5) the need for a partial award (people) affect the team's performance follow-up; and (6) self-actualization needs partially (individual) effect on the performance of the team follow-up.